334 PROTEIN KINASE EXPRESSION PROFILING IN HUMAN TRISOMY: GENE DOSAGE AND AMPLIFIED INSTABILITY. (1st January 2006) - Yong, P. J.; McFadden, D. E.; MacCalman, C. D.; Robinson, W. P.
Abstract : Introduction: Trisomy is the cause of Down syndrome (trisomy 21) and is present in one in four spontaneous abortions (SAs), the most frequent (5-10%) being trisomy 16. In the gene dosage hypothesis, the trisomic phenotype is due to overexpression of specific genes on the trisomic chromosome, such that different trisomies will have different patterns of gene expression. In the amplified instability hypothesis, the trisomic phenotype is due to the extra chromosome disrupting cellular homeostasis non-specifically (ie, regardless of chromosome type), which causes an amplified sensitivity to interindividual environmental and genetic variation, such that trisomy will show increased interindividual variability in gene expression. Methods: Protein kinases ( n = 75), fundamental components of signal transduction, were profiled in placental chorionic villus cultures from first-trimester SAs: trisomy 16 (T16) ( n = 3), trisomy 15 (T15) ( n = 3), and euploid (Eu) ( n = 4). Protein and RNA expression were profiled with a 2D Western blot and 14, 000 oligonucleotide array. Immunochemistry showed all cultures consisted of fibroblasts. Maternal decidual contamination was ruled out by microsatellite PCR. Results: At the protein level, 7 kinases had significantly different expression ( p < .05) in T16 vs Eu (CDK1, CDK7, PKC-", PKG1, ERK1, S6K p70, IKK-α), of which 2 were also different in T15 vs Eu (S6K p70, IKK-α). Seven kinases were only different in T15 vs Eu (CK1-", SRC, CDK9, DNAPK, MEK2, PKC-z, PKC-β). Interestingly, 13 of these total 16 differences involved lower expression in the trisomy (Sign test, p = .021). For the kinases with genes on chromosome 16 or 15, only ERK1 (16p11) was significantly overexpressed (at both the RNA and protein levels) in the trisomic state. In addition, the coefficient of variation (V) was used to quantify interindividual variability in gene expression. At the protein level, V was significantly higher in T16 (V = 0.49) and T15 (V = 0.52) compared to Eu (V = 0.28) (both p < .001); but at the RNA level, V was lower in T16 (V = 0.19) and T15 (V = 0.25) compared to Eu (V = 0.32) (p < .001, p = .02). Conclusions: The differential expression pattern between T16 and Eu, distinct from the pattern between T15 and Eu, as well as the dose-related increase in ERK1 expression in T16, supports the gene dosage hypothesis. The high V for both trisomies at the protein level supports the amplified instability hypothesis, although it was not initiated at the RNA level, suggesting a (post)-translational origin. This study provides evidence that the mechanisms of gene dosage and amplified instability can operate simultaneously in human trisomy.